Analysis Of Factors Affecting Students' (Vocational High School) Interest In Decision Making In Choosing Accounting Study Programs At Higher Education Institutions (Case Study Of Private Vocational High Schools In Palembang City - Purnama Sari; Titin Vegirawati; Hadli Hadli (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The level of interest of students (vocational high school) in choosing accounting study programs in college is still very low. This is influenced by several factors such as learning motivation, socio-economic status, environment, job opportunities, and student interests. This study aims to determine the effect of learning motivation, socio-economic status, job opportunities, on student interest (vocational high school) in choosing accounting study programs in college. The data analysis technique uses partial least squares (PLS) with the warp pls 4.0 approach. The population is 724 and the number of samples in this study is 224 students. The results of the analysis state that learning motivation influences students' interest in choosing accounting study programs in college because the p-value is above 0.5, job opportunities influence the interest of vocational high school students in choosing accounting study programs in college, socio-economic status does not influence students' interest in choosing accounting study programs in college, and the environment does not influence students' interest in choosing accounting study programs in college.